Saúde bucal do binômio mãe-filho: aspectos clínicos, sócio-comportamentais e qualidade de vida - Rocha, Najara Barbosa da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The mother has fundamental role on her child´s development; she´s responsible for the adoption of health habits, which reduce factors associated with oral diseases on the child. The goals, on this study, were to analyses the maternal oral health, quality of life and other factors that interfere on development of tooth decay on children. An analysis was done on a longitudinal, prospective study from pregnancy to 4 years of age. The sample was made of pregnant women on their third trimester of pregnancy, served in the public health service, who were interviewed subjected to clinical oral exams. The children were observed, after birth in their homes to 4 years of age, subjected to clinical oral exams. The questionnaires used were semi-structured calibrated in a pilot study with oral health perception and OHIP-14. The variables studied were: mother and child´s oral health, socioeconomic status and behavioral condition, the impact of the oral health on the quality of life and perception of the mother about the child´s oral health. Bivariate statistical analyzes were performed, of correlation and multivariate logistic regression. The pregnant women (n=116) were, in average, 25 years old (±5.8), the majority worked (54.3%), had less than 12 years of schooling (93.1%), lived with their partners (80.2%) and had low-income (90.5%). The average CPO index of such mothers was of 12.1(±6.3) ; the majority needed some type of prosthesis (56.0%), presented gum alteration (91.9%), decayed teeth (68.9%), need of some kind of treatment (66.4%) and periodontal attachment loss to 3mm (75.3%). The OHIP-14 average was of 5.11, being that the higher impact of oral health, in quality of life, was associated with the need for prosthesis (p<0.01), need of treatment (p<0.01), decay (p<0.01) and lost teeth (p<0.01). Children (n=73) were, in its majority female...

A mãe exerce papel fundamental no desenvolvimento da criança; é responsável pela adoção de hábitos saudáveis, que reduzem os fatores de risco para doenças bucais no filho. Os objetivos, neste estudo, foram analisar a saúde bucal materna, qualidade de vida e fatores que interferem no desenvolvimento de cárie dentária em crianças. Foi realizado um estudo longitudinal, prospectivo, da gestação até quatro anos de idade das crianças. A amostra foi composta por gestantes que estavam no terceiro trimestre e atendidas nos serviços públicos de saúde, as quais foram entrevistadas e submetidas a exames clínicos bucais. As crianças foram observadas, após o nascimento em seus domicílios até os quatro anos de idade, realizados os exames clínicos bucais. Os questionários utilizados foram: semi-estruturado calibrado em estudo piloto, com percepção sobre saúde bucal e OHIP-14. As variáveis estudadas foram: saúde bucal da mãe e do filho, condição socioeconômica e comportamental, impacto da saúde bucal na qualidade de vida e percepção da mãe sobre sua saúde bucal e de seu filho. Foram realizadas análises estatísticas bivariadas, de correlação e regressão logística multivariada. As gestantes (n=116) tinham idade média de 25 (±5,8) anos, em sua maioria trabalhavam (54,3%), tinham menos de 12 anos estudados (93,1%), moravam com companheiro (80,2%) e eram de baixa renda (90,5%). O índice CPO médio das mães foi de 12,1(±6,3); a maioria necessitava de algum tipo de prótese (56,0%), apresentaram alteração gengival (91,9%), dentes cariados (68,9%), necessidade de tratamento (66,4%) e perda de inserção de até 3 mm (75,3%). A média do OHIP-14 foi de 5,11, sendo que o maior impacto da saúde bucal, na qualidade de vida, esteve associado com necessidade de prótese (p= 0,00), necessidade de tratamento (p=0,00), presença...
Keywords: Qualidade de vida; Estudos longitudinais; Saúde bucal; Fatores de risco; Cáries dentárias; Dental caries